The Interplay between the Unfolded Protein Response, Inflammation and Infection in Cystic Fibrosis - Pascal Trouvé; Claude Férec; Emmanuelle Génin (Cells, 2021)
In cystic fibrosis (CF), p.Phe508del is the most frequent mutation in the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene. The p.Phe508del-CFTR protein is retained in the ER and rapidly degraded. This retention likely triggers an atypical Unfolded Protein Response (UPR) involving ATF6, which reduces the expression of p.Phe508del-CFTR. There are still some debates on the role of the UPR in CF: could it be triggered by the accumulation of misfolded CFTR proteins in the endoplasmic reticulum as was proposed for the most common CFTR mutation p.Phe508del? Or, is it the consequence of inflammation and infection that occur in the disease? In this review, we summarize recent findings on UPR in CF and show how infection, inflammation and UPR act together in CF. We propose to rethink their respective role in CF and to consider them as a whole.